Experience and Management of Fear in Men's World Cup Alpine Ski Racing - Rogers, Morgan; Paskevich, David (Frontiers in Psychology, 2021)
Alpine ski racers, specifically in the discipline of downhill, may experience fear competing in such a high-risk environment. The purpose of this study was to explore Canadian national team men’s experience and management of fear in World Cup alpine ski racing. This study uses an interpretive phenomenological analysis, conducted with five male members of the Canadian national ski team. Three themes emerged: contextual influences, preparation and process, and risk vs. reward. The findings indicate one’s experience and management of fear may be influenced by contextual factors (e.g., weather, course profile) and confidence, and that confidence is influenced by the same situational factors that influence fear as well as athlete preparation. There currently exists a discrepancy between the athletes’ approaches to training and racing, making it difficult to master fear management strategies. As a result of the discrepancy created between training and racing, there are several implications for how the national team environment and training is structured, and we present recommendations for how these findings can be applied to training.